Heavy Fuel Treatment As The Main Fuel On Board - Suwarso Suwarso; Yuni Mariah; Sunarto Sunarto (Jurnal Indonesia Sosial Teknologi, 2023)
One of the important factors in the smooth operation of the ship is the use of heavy fuel. Heavy fuel is cheaper than the price of diesel oil which is used as fuel for the main driving engine. Main Machine Tools often experience interference due to fogging of the fog, wear between the liner and the piston spring or other parts due to lack of proper maintenance and understanding. This research is survey research, which is field research and asks for the opinions of respondents who take samples from a population and use interviews or question lists as a basic data collection tool. Maintenance and maintenance of fuel in its implementation carried out regularly will be able to prevent more severe damage and decrease engine work. Integrated fuel handling and maintenance will facilitate the operation of the ship. Where in the effort of regular maintenance and maintenance and planning will extend the operating life of the ship. Maintenance and maintenance of fuel in its implementation carried out regularly will be able to prevent more severe damage and decrease engine work